Evaluasi Kebijakan Kartu Identitas Anak (KIA) Di Dinas Kependudukan Dan Pencatatan Sipil Kota Bengkulu - Agustin, Ade; Saputra, Harius Eko; Rikardo, Yanuar (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
The Child Identity Card (KIA) is a program launched by the Directorate General of Population and Civil Registration (Ditjen Dukcapil) in accordance with Permendagri Number 2 of 2016 concerning KIA, implementation at Disdukcapil of Bengkulu City on January 01, 2019. KIA is the same identity card as KTP, in its implementation KIA is given to children aged 0-17 years as proof of identity, but in 2023 the achievement of KIA was only 51.31% of the national achievement target of 75%. The purpose of this study is to evaluate the Child Identity Card (KIA) Policy at the Population and Civil Registration Office of Bengkulu City, with the Evaluation theory using Wayne Parsons' theory in Utari (2021: 30), namely Formative Evaluation and Summative Evaluation. Using Qualitative Research Methods with 5 informants. Data collection techniques using primary data and secondary data, based on the results of the study, it is known that it is not quite optimal: seen from the aspect of target achievement, it has not yet reached the target, there has been no socialization by invitation to the sub-district and village communities, but has worked with schools, hospital midwives, and RT / Urban Village. The budget factor is the lack of budget in the implementation of the MCH program, thus making the socialization (communication, information, and education) not running optimally. In terms of services, it has been carried out in accordance with applicable standard service procedures, from the aspect of resources it is still lacking but in terms of quality it is adequate, and in terms of the impact of benefits before and after the KIA program was implemented, previously there was no child identity card that could be carried everywhere similar to Identity Card as proof of the child's identity when experiencing adverse events and making it easier for children to gain access to public services such as in the fields of education, health, banking, transportation and immigration.